Vitamin D pathway gene variation rs3740165 is associated with serological uric acid levels in healthy Chinese women - Gu, Jiemei; Yue, Hua; Wang, Chun; Zhang, Hao; Hu, Weiwei; Zhang, Zhenlin (Frontiers in Endocrinology, 2022)
Aim: To investigate the relationship between gene polymorphisms involved in the vitamin D metabolic pathway and serum uric acid (UA) levels in Chinese women. Methods: Fifteen key genes within the vitamin D metabolic pathway were screened using 96 single nucleotide polymorphisms in a group of 1,206 (37.96±13.08 years) unrelated healthy Chinese women (aged 20–85 years). Blood and urine tests were performed at the same time. The Wilcoxon Mann–Whitney test was used to compare groups aged ≤50 years and >50 years. The mean serum UA values were computed within each group of homozygous referent, heterozygous, and homozygous variant genotypes for each single nucleotide polymorphism. Results: The exclusion process left 1,169 participants (38.16±13.13 years) for analysis. One single nucleotide polymorphism in the CUBN gene (rs3740165) was identified as being significantly associated with serum UA levels in the group aged over 50 years. The wild type (C/C) population had higher serum UA levels in this group (P<0.001). In women aged over 50 years, allele C was associated with a higher risk of hyperuricemia than allele T (odds ratio 2.752, 95% confidence interval 1.458–5.192; P = 0.002). There was also a higher risk of hyperuricemia in genotype TC + CC compared with genotype TT (odds ratio 3.326, 95% confidence interval 1.513–7.313; P = 0.003) in women over 50 years of age. Conclusion: The results suggest that the CUBN gene contributes to variability in serum UA levels in healthy Chinese Han women over 50 years of age.